Infant formula and enamel fluorosis A systematic review - Hujoel, Philippe P.; Zina, Livia G. [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Cunha-Cruz, Joana (Amer Dental Assoc, 2009)
Background Researchers have considered infant formula consumption a potential risk factor for enamel fluorosis in the U.S. population. The authors conducted a systematic review of controlled studies regarding the risk of developing enamel fluorosis associated with use of infant formula.Methods. One reviewer independently conducted systematic searches in eight databases. The authors then abstracted information, assessed study quality and combined odds ratios (ORs), when obtainable, by using a random-effects model.Results. After evaluating 969 potentially eligible published studies, the reviewers found that the authors of 41 studies had evaluated the effect of infant formula on enamel fluorosis risk. Authors of 14 of the 41 studies did not report their findings in their results. The authors of the remaining 27 published studies reported the findings of 19 observational studies; authors of 17 of these 19 studies reported ORs and, among these, infant formula consumption was associated with a higher prevalence of enamel fluorosis in the permanent dentition (summary OR 1.8, 95 percent confidence interval [CI] 1.4-2.3). There was significant heterogeneity among studies (I(2) 66 percent) and evidence of publication bias (P=.002). A metaregression analysis indicated that the ORs associating infant formula with enamel analysis indicated by 5 percent for each 0.1-part-per-million increase in the reported levels of fluoride in the water (OR 1.05, 95 percent CI 1.02-1.09).Clinical Implications. Infant formula consumption may be associated with an increased risk of developing at least some detectable level of enamel fluorosis, which depends on the level of fluoride in the water supply. The evidence that the fluoride in the infant formula caused enamel fluorosis was weak, as other mechanisms could explain the observed association.
Keywords: Infant formula; fluorosis; mottled teeth